Load case selection technique for combined modal finite element approach of high aspect ratio wing models - Nordin, Norzaima; Bohari, Baizura; Chandrasegaran, Thinesh; As’arry, Azizan; Harmin, Mohammad Yazdi (National Cheng Kung University, 2023)
A high aspect ratio wing is known to exhibit high deflection even at relatively low aerodynamic loading, making it susceptible to geometric nonlinearity. However, integrating linear and nonlinear static solutions through conventional finite element demands significant time and effort. Therefore, researchers have been exploring the use of nonlinear reduced order model to improve computational efficiency, allowing for faster and more accurate prediction of system behaviour. One option to enable this is through the combined modal finite element approach. However, to date, there are limited guidelines on the generation of load cases to develop this approach. Therefore, this paper proposes a load case selection method as part of the combine modal finite element procedure, which initiates with normal mode selection and continues with loading profile selection technique, either using individual or combined modes. The results show that the current approach can predict deflection with reasonable accuracy compared to conventional finite element, with small mean error and low standard deviation. Moreover, developing the loading profile based on combined modes is exceptionally accurate and required less computational time. Hence, the proposed methodology can be considered a way forward in developing reduced order model approach for future works related to highly flexible wing systems.